Low Protein Diets Supplemented With Alpha-Ketoglutarate Enhance the Growth Performance, Immune Response, and Intestinal Health in Common Carp (Cyprinus carpio) - Wu, Di; Fan, Ze; Li, Jinnan; Zhang, Yuanyuan; Xu, Qiyou; Wang, Liang; Wang, Liansheng (Frontiers in Immunology, 2022)
To investigate the effects of alpha-ketoglutarate (AKG) supplementation in a low protein (LP) diet on the growth performance, immune response, and intestinal health of common carp (Cyprinus carpio), 600 carp were randomly divided into five dietary groups: a normal protein (NP) diet containing 32% crude protein, an LP diet formulated with 28% crude protein, and LP with AKG at 0.4%, 0.8%, and 1.2% (dry matter). After an 8-week trial period, the results demonstrated that an LP diet led to a decrease in performance, immune response, and intestinal barrier function. Compared with the LP group, the final body weight and weight gain rate in the LP+0.4% AKG group were significantly higher, the feed conversion ratio was significantly decreased with the addition of 0.4% and 0.8% AKG. The supplementation with 0.4% and 0.8% AKG markedly increased the activities of T-SOD and GSH-Px, as well as the expression levels of GPX1a and GPX1b relative to the LP group, whereas the MDA content was significantly decreased in the LP+0.4% AKG group. In addition, the expression levels of tight junctions including claudin-3, claudin-7, ZO-1, and MLCK were significantly up-regulated in the LP+0.4% AKG group, and the relative expression levels of the pro-inflammatory factors IL-1β and IL-6α were significantly lower with the addition of 0.4%, 0.8%, and 1.2% AKG. Moreover, the abundance of Proteobacteria in the LP+0.4% AKG group was lower than that in the LP group, and the abundance of Firmicutes and Fusobacteria was higher at the phylum level. The abundance of Citrobacter in the LP+0.4% AKG group was decreased compared to the LP group, while the abundance of Aeromonas was increased at the genus level. In short, the effects of AKG on the intestinal health of the common carp were systematically and comprehensively evaluated from the perspectives of intestinal physical barrier, chemical barrier, biological barrier, and immune barrier. We found that an LP diet supplemented with 0.4% AKG was beneficial to the growth performance and intestinal health of common carp.